2007
DOI: 10.1371/journal.pbio.0050196
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Reciprocity in Rats

Abstract: The evolution of cooperation among nonrelatives has been explained by direct, indirect, and strong reciprocity. Animals should base the decision to help others on expected future help, which they may judge from past behavior of their partner. Although many examples of cooperative behavior exist in nature where reciprocity may be involved, experimental evidence for strategies predicted by direct reciprocity models remains controversial; and indirect and strong reciprocity have been found only in humans so far. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
303
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(313 citation statements)
references
References 43 publications
(51 reference statements)
5
303
2
3
Order By: Relevance
“…It should further be noted that in contrast to previous experimental studies on animal reciprocity (39)(40)(41)(42), there was a distinct cognitive dimension to the current task-that is, chimpanzees did not merely respond to the outcome of the partner's actions but Fig. 2.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It should further be noted that in contrast to previous experimental studies on animal reciprocity (39)(40)(41)(42), there was a distinct cognitive dimension to the current task-that is, chimpanzees did not merely respond to the outcome of the partner's actions but Fig. 2.…”
Section: Discussionmentioning
confidence: 71%
“…One possibility, for instance, is that costly prosocial acts are contingent on others' prior helpful behaviors (37,38) and therefore could not be detected in experiments stripped of any prior cooperative interaction. Indeed, several studies have suggested reciprocal patterns of sharing behaviors in the animal kingdom (39)(40)(41)(42), although the underlying psychological mechanisms are not always clear. Although chimpanzees did not show such reciprocal prosocial patterns in some experiments (43,44), this can at least partly be explained by the subjects' lack of understanding of experimental setup and the choice contingencies (see refs.…”
mentioning
confidence: 99%
“…For instance, in experimental situations, animals are generally forced to interact with a given partner, whereas under natural conditions, they can choose or refuse partners, based on their level of attachment toward them or even on their reputation (e.g. Rutte & Taborsky 2007. We recommend, therefore, that future studies be conducted in more natural situations, to evaluate how widespread reciprocal altruism is among animals.…”
Section: Discussionmentioning
confidence: 99%
“…Generalized reciprocity results when B helps C because A helped B independently of the identity of individuals (Hamilton and Taborsky, 2005a;Pfeiffer et al, 2005;Rutte and Taborsky, 2007). There is evidence for generalized reciprocity in humans (Yamagishi and Cook, 1993) and rats (Rutte and Taborsky, 2007).…”
Section: Generalized Reciprocitymentioning
confidence: 99%
“…There is evidence for generalized reciprocity in humans (Yamagishi and Cook, 1993) and rats (Rutte and Taborsky, 2007). It is related to kin selection because, ultimately, both rely on positive assortment of co-operators (Hamilton, 1975;Hamilton and Taborsky, 2005a;Lehmann and Keller, 2006).…”
Section: Generalized Reciprocitymentioning
confidence: 99%